User-centered design and usability testing of RxMAGIC: a prescription management and general inventory control system for free clinic dispensaries - Arielle M. Fisher; Timothy M. Mtonga; Jeremy U. Espino; Lauren J. Jonkman; Sharon E. Connor; Nickie K. Cappella; Gerald P. Douglas (BMC, 2018)
Abstract Background To address challenges related to medication management in underserved settings, we developed a system for Prescription Management And General Inventory Control, or RxMAGIC, in collaboration with the Birmingham Free Clinic in Pittsburgh, Pennsylvania. RxMAGIC is an interoperable, web-based medication management system designed to standardize and streamline the dispensing practice and improve inventory control in a free clinic setting. This manuscript describes the processes used to design, develop, and deploy RxMAGIC. Methods We transformed data from previously performed mixed-methods needs assessment studies into functional user requirements using agile development methods. Requirements took the form of user stories that were prioritized to drive implementation of RxMAGIC as a web-application. A functional prototype was developed and tested to understand its perceived usefulness before developing a production system. Prior to deployment, we evaluated the usability of RxMAGIC with six users to diagnose potential interaction challenges that may be avoided through redesign. The results from this study were similarly prioritized and informed the final features of the production system. Results We developed 45 user stories that acted as functional requirements to incrementally build RxMAGIC. Integrating with the electronic health record at the clinic was a requirement for deployment. We utilized health data standards to communicate with the existing order entry system; an outgoing electronic prescribing framework was leveraged to send prescription data to RxMAGIC. The results of the usability study were positive, with all tested features receiving a mean score of four or five (i.e. somewhat easy or easy, respectively) on a five-point Likert scale assessing ease of completion, thus demonstrating the system's simplicity and high learnability. RxMAGIC was deployed at the clinic in October 2016 over a two-week period. Conclusions We built RxMAGIC, an open-source, pharmacist-facing dispensary management information system that augments the pharmacist's ability to efficiently deliver medication services in a free clinic setting. RxMAGIC provides electronic dispensing and automated inventory management and alerting capabilities. We deployed RxMAGIC at the Birmingham Free Clinic and measured its usability with potential users. In future work, we plan to continue to measure the impact of RxMAGIC on pharmacist efficiency and satisfaction.